Elementary Students' Knowledge Development during the Implementation of "After School Exercise" Program - Ioannis Syrmpas; Marios Goudas (MDPI AG, 2021)
Physical education should focus not only on students' motor and emotional development but also on their cognitive development. The purpose of the present study was to examine whether elementary students' health-related knowledge and physical activity-related goal setting increased after they participated in a program. The program aimed at promoting after school physical activity among students. Participants were 244 fifth- and sixth-grade students (116 boys and 128 girls). Students' knowledge was examined by means of a multiple-choice test, cognitive assignments and a retrospective pre-post questionnaire. The results from the three measures indicated that students enhanced their knowledge both regarding the health benefits of physical activity (PA) and effective goal setting. Hence, it can be argued that the program was effective in promoting students' skills and knowledge related to PA.